Technology forces at work : profiles of environmental research and development at Dupont, Intel, Monsanto, and Xerox - Resetar, Susan A., 1961- (RAND, 1999)
Not too long ago industry almost monolithically viewed environmental considerations as an expense--sometimes as a nuisance. That is beginning to change. Industry leaders now see the advantage of going beyond complying with environmental regulations, as had been their wont, and incorporating the search for environmentally sound business practices into their research and development. This report features case studies of four industry leaders--DuPont, Intel, Monsanto, and Xerox--and discusses how these companies view environmental technology investments. The information is based on a series of interviews with senior R & D managers and environment, health, and safety personnel along with the relevant literature. At the request of the Office of Science and Technology Policy in the Executive Office of the President, the authors have provided the views of a subset of one of the key stakeholders in environmental policy, industry, which have heretofore not received a lot of emphasis.